Evaluation of the proacrosin / acrosin system and its mechanism of activation in human sperm extracts - Zahn, Astrid (2002)
Acrosin is an acrosomal protease synthesized as a proenzyme and activated into beta-acrosin during the acrosome reaction. In the present study, a set of sensitive assays was developed to identify the proacrosin/acrosin system and to evaluate its activation pattern in human sperm extracts. Immunocytochemical analysis with monoclonal antibody (Mab) AcrC5F10 showed specific staining on the acrosome of permeabilized ejaculated and capacitated spermatozoa. Acrosome reaction was associated with a decrease in staining. AcrC5F10 specifically recognized a 55-kDa band (proacrosin) in Western immunoblots. Activation studies showed enzymatically active intermediates of 39 and 35 kDa after zymography. Immunoreactive bands of 52, 43, 34, 21-26 and 16 kDa were identified in the activation patterns developed with AcrC5F10. Activation was completely inhibited in the presence of 9 mM CaCl(2) or 100 mM benzamidine. A multiple sequence alignment revealed partial conservation of putative cleavage sites in the proacrosin sequence. The tests described allow the detection of human proacrosin in spermatozoa and sperm protein extracts, as well as the evaluation of the proenzyme activation pattern. They can be used to study the effect of inhibitors upon proenzyme activation. In addition, alterations in proacrosin activation in semen samples with abnormal acrosin enzymatic activity can be analyzed using these assays.